Эхокардиографическая оценка систолической экскурсии плоскости трикуспидального кольца в различных возрастных категориях в норме - Салахова, А.М.; Четверик, А.Н. (Таврический медико-биологический вестник, 2013)
У ході дослідження вивчено можливість ехокардіографічної оцінки функції правого шлуночка серця
з використанням такого параметра, як систолічна екскурсія площині трикуспідального кільця (TAPSE –
tricuspid annular plane systolic excursion). Показано, що судження про виражену дисфункцію правого
шлуночка при зниженні систолічної екскурсії кільця тристулкового клапана менше 2,0 см, не вірне в
педіатричній практиці. Наведено нормальні показники TAPSE в різних вікових категоріях, що дозволяє
використовувати даний ехокардіографічний параметр для вивчення систолічної функції правої шлуночкової
камери при різних патологічних станах, насамперед при легеневої гіпертензії. The aim of our work was the study the systolic excursion of the tricuspid valve in healthy children from
newborn to 18 years. Normal parameters of TAPSE are given in different age categories. According to received
information TAPSE in newborns normally be in the range of 0.75 cm to 1.15 cm. Tricuspid annular plane excursion
increases with age. On average, only in 8 years children TAPSE is approaching the value of 1.8 cm. This value in
adults is taken as the lower limit of normal. It should be noted that in 17–18 years TAPSE closes to the generally
accepted norm in adults. Thus, TAPSE is an informative parameter to study the right ventricle function, and now
it also can be used for dynamic monitoring and prediction of outcomes in children with high blood pressure in
pulmonary artery.